The ethology, sociology and interspecific interactions of the yellow mongoose, Cynictis Penicillata, in the Karoo - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2024)
Dissertation (MSc )--University of Pretoria, 1994.